Imagen del destino y el comportamiento del vacacionista que visitan el Centro de Rescate Amazónico Iquitos 2025 - Guzman Ruiz, Geraldine Sofia (2025)
The purpose of this research was to establish the relationship between "Destination Image" and "Vacationer Behavior" at the Iquitos Amazon Rescue Center during the year 2025. This quantitative, descriptive, and correlational study employed a non-experimental design. The sample consisted of 40 vacationers, and Spearman's Rho coefficient was used to evaluate the correlation between variables. The results indicated high measurement reliability, evidenced by a Cronbach's Alpha coefficient of 0.975 for "Destination Image" and 0.959 for "Vacationer Behavior." A moderate and significant correlation was found between both variables (ρ = 0.513, p = 0.001), confirming the hypothesis that a positive destination image is linked to more favorable vacationer behavior. These results highlight the importance of strengthening destination perceptions to promote more satisfying tourism with a higher likelihood of repeat visits.